ANTIMICROBIAL RESISTANCE CONTROL PROGRAM ON THE RATIONAL USE OF ANTIBIOTICS IN EKA HOSPITAL PEKANBARU, INDONESIA - Rosinta Magdalena; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Antimicrobial resistance (AMR) threatens the effective prevention and treatment of an ever-increasing range of infections caused by bacteria, parasites, viruses and fungi. Rational use of antibiotics can reduce the emergence of antimicrobial resistance, cost of treatment, length of stay in hospitals, and improve health outcomes. This study aims to analyse the output of AMR control program implementation on the rational use of antibiotics in hospitals. Method: This research is a retrospective study, using descriptive analysis with Gyssens' algorithm. Data were assessed from the medical records of patients treated at Eka hospital in 2017. The number of samples 877, in the ICU wards amounted to 307 and Hopea B 570. The analysis was performed by assessing the suitability of antibiotic therapy. The results are presented in therapeutic terms: the antibiotics used and the percentage of use based on the Gyssens algorithm. Result:The results of data analysis found there is an increase in the rationality of the use of antibiotics on the unit ICU (67.77%), Hopea B (67.36%). There is a decrease in Patients Length of Stay (LOS) in ICU (26%), in Hopea B (58%). The level of antibiotic use without indication in ICU (8.82%). in the Hopea B ward (5.34%.). Attitude of non-compliance of doctors against hospital guidelines and inadequate monitoring of antibiotic therapy. In the case of prophylactic antibiotics remain unobserved because of the lack of pharmacists who can monitor their use. Conclusion: Eka Hospital has established an AMR Control program, but it has not been implemented properly. Continuous evaluation, awareness raising and understanding of doctors, the addition of monitoring officers (pharmacists), patient screenings and hospital staff on an ongoing basis, are worthy of consideration in order to improve the implementation of the program.